2014
DOI: 10.1590/s1679-45082014ao2932
|View full text |Cite
|
Sign up to set email alerts
|

SeptiFast for diagnosis of sepsis in severely ill patients from a Brazilian hospital

Abstract: ObjectiveTo test and validate a multiplex real-time polymerase chain reaction method for bloodstream infections, as well as to compare the results with conventional blood culture.MethodsA total of 114 consecutive patients with clinical evidence of sepsis were submitted to blood culture and LightCycler™ SeptiFast tests.ResultsMore positive specimens (23; 20.2%) were detected using the LightCycler™ SeptiFast than the blood culture (17; 14.9%), with an agreement of 86.8%. Discordant results were seen in four pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
7

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
0
5
0
7
Order By: Relevance
“…45,69,[71][72][73][74][75][76][77][78][80][81][82][83][85][86][87][90][91][92][93][94][96][97][98][99][101][102][103]107,[109][110][111][112]114 Of these, nine studies reported blood volumes that did not comply with CE approval: Lehmann et al, 76 Lodes et al 92 and von Lilienfeld-Toal et al 71 all reported using 1 ml in adults; Bloos et al, 74 Lamoth et al, 75 Paolucci et al 99 and Sitnik et al 107 all reported using 3 ml in adults; Berger et al…”
Section: Details Of Index and Reference Tests Blood Sampling Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…45,69,[71][72][73][74][75][76][77][78][80][81][82][83][85][86][87][90][91][92][93][94][96][97][98][99][101][102][103]107,[109][110][111][112]114 Of these, nine studies reported blood volumes that did not comply with CE approval: Lehmann et al, 76 Lodes et al 92 and von Lilienfeld-Toal et al 71 all reported using 1 ml in adults; Bloos et al, 74 Lamoth et al, 75 Paolucci et al 99 and Sitnik et al 107 all reported using 3 ml in adults; Berger et al…”
Section: Details Of Index and Reference Tests Blood Sampling Methodsmentioning
confidence: 99%
“…Twenty-one SeptiFast studies reported data on the time to availability of results/pathogen identification. [44][45][46]59,60,64,68,69,77,80,81,85,88,93,96,97,101,106,107,110,112 However, for the majority of these studies, it was unclear if the value was the mean or median, and variance estimates or ranges were not reported. Across these studies, the reported time to pathogen identification with SeptiFast ranged from 4 hours 68 to a median of 26.25 hours [range 6.75-79 hours (for samples collected at beginning of a weekend)].…”
Section: Assessment Of Clinical Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Como a doença é uma das maiores causas de mortalidade no mundo, com incidência estimada de até 19 milhões de pessoas por ano (GUIDO et al, 2016), consequentemente, é um dos principais problemas de saúde pública (TORIO; ANDREWS, 2013). De modo geral, possui alta mortalidade no Brasil, alcançando quase 60% dos casos, enquanto a média mundial está em torno de 30% (SITNIK et al, 2014;SIQUEIRA-BATISTA et al, 2011).…”
Section: Introductionunclassified
“…The detection of the pathogen by this molecular diagnostic tool permits the rapid diagnosis of bacteremia/ fungemia and an earlier administration of appropriate antibiotic therapy. 112,113 The detection limit is 100 CFU/mL for Candida glabrata, Streptococcus spp., and coagulase-negative Staphylococcus, and ranges from 3 to 30 for the others, depending on the infective agent. 114 Limitations include its high cost (150-200 € per test), trained personnel requirement, and lack of information on antibiotic sensitivity.…”
mentioning
confidence: 99%